Influence of recycled concrete aggregate treatment methods on performance of sustainable warm mix asphalt. Issue 1 (1st January 2020) - Abass, Bedour J.; Albayati, Amjad H.
Abstract: This study aimed to investigate the usability of Recycled Concrete Aggregate (RCA) in warm mix asphalt (WMA) as the implementation of sustainable construction technology. Five replacement rates (0%, 25%, 50%, 75%, and 100%) were tested for the coarse fraction of virgin aggregate (VA) with 3 types of RCA: untreated RCA, HL-treated RCA, and HCL-treated RCA. Scanning electron microscopy (SEM) analyses were performed to investigate the surface morphology for both treated and untreated RCA. The optimum asphalt cement content for every substitution rate was determined using Marshall mix design method. Thereafter, asphalt concrete specimens were prepared using the optimum asphalt cement content, followed by the evaluation of their performance properties, including the moisture damage, resilient modulus, and permanent deformation characteristics. These properties were assessed using indirect tensile strength and uniaxial repeated loading tests, respectively. It was found that, for mixes with RCA content of 100%, the untreated RCA mixes possess higher OAC than that of treated RCA mixes by 0.26%. The moisture susceptibility was improved in case of HL and HCL treated RCA by 9.09% and 10.34% as compared to untreated RCA. However, the resilient modulus and resistance to permanent deformation for the mixes with 100% RCA were lower than those prepared with VA; the decrement in Mr values are 39.17%, 28.56% and 23.09% for the untreated RCA, HL-treated RCA and HCL-treated RCA, respectively. Finally, the cost, material, and energy-saving implications of RCA were discussed.